Численное моделирование микрофизических и электрических характеристик конвективных облаков - Белый, Т.А.; Шпиг, В.М. (Геоінформатика, 2016)
Рассмотрены результаты численного моделирования катастрофических осадков, вызвавших сильные паводки над восточной частью Крыма в сентябре 2002 г. Исследуется влияние электрического поля на эффективность столкновения заряженных капель как одного из механизмов резкого увеличения осадков. Получены численные оценки изменения микрофизических характеристик облачности без учета электрических сил и с их учетом. На основе эмпирических зависимостей сделан вывод о возможности быстрого образования зародышей осадков вследствие коагуляционных процессов и взаимодействия заряженных капель в сильных электрических полях в облаке. Показано, что электрическая коагуляция в электрических полях ~10³ В/см существенна и ее нужно учитывать при моделировании мощных конвективных облаков, находящихся на стадии максимального развития. Розглянуто результати чисельного моделювання катастрофічних опадів, які спричинили сильні паводки над східною частиною Криму у вересні 2002 р. Досліджено вплив електричного поля на ефективність зіткнення заряджених крапель як одного з механізмів різкого збільшення опадів. Отримано чисельні оцінки зміни микрофізичних характеристик хмарності без урахування електричних сил та з їх урахуванням. На основі емпіричних залежностей зроблено висновок щодо можливості швидкого утворення зародків опадів унаслідок коагуляційних процесів і взаємодії заряджених крапель у сильних електричних полях у хмарі. Показано, що в електричних полях ~10³ В/см електрична коагуляція є суттєвою і її потрібно враховувати під час моделювання потужних конвективних хмар, які перебувають на стадії максимального розвитку. Purpose. At the present time interconnection and interdependence of electrical and non-electrical processes in cumulonimbus clouds are not sufficiently clear. Thus the purpose of the paper is to investigate the influence of the electric field on the effectiveness of the collision of charged droplets, as one of the mechanisms of a sharp increase in precipitation. The development of numerical models of clouds and the study on their basis of various issues of cloud and precipitation, as well as the electrical processes that affect the coagulation of cloud particles are important for resolving scientific and applied problems.
The methodology is based on the use of complex three-dimensional diagnostic and prognostic models of frontal clouds initiated by the atmosphere sounding data. The prediction model includes the integral-differential equations with a detailed description of the thermodynamic and microphysical processes.
Findings. With the help of 3D prediction model of frontal clouds, we investigated the feedback mechanism between the enlargement of the particles in the cloud and the increase of the electric field potential gradient. A series of numerical experiments were carried out to investigate the relationship of microphysical characteristics and electrical processes in the clouds. When account was taken of electric coagulation, a significant impact was observed on the distribution of microphysical characteristics of convective clouds, leading to an expansion of the area of a liquid-drop part of cloud and the increase of the values of liquid water content. The maximum water content increased from 0.32 to 0.63 g/kg (in the case when electric processes were taken into consideration). We also obtained a decrease of the cloud base.
The spatial distribution of ice crystals also changed. We observed a formation of a single powerful structure of large vertical extent, as well as the decrease of the lower level of the presence of crystals, in contrast to the calculations results that we got when electrical processes were ignored. Concurrently, the decrease was obtained for maximum concentration values of crystals: from 3.6·10³ to 3.1·10³l/g. Electric coagulation contributed to the increase of negative values of the potential gradient and the decrease of its positive values. Negative values of E increased by 700 V/cm, and its positive values decreased by 200 V/cm.
Practical value and conclusions. The increase of cloud power, normally tends to increase its electric nonuniformity. It was found that electric coagulation leads to a redistribution of cloud particles, increasing the water content of convective clouds, which brings about significant changes in the structure of the spatial distribution of the cloud crystals concentrations. The smaller the radius of the droplets the greater the influence of electric charges, the mechanism described in the paper may possibly be the main factor (in combination with the gravitational particle growth) in fast formation of heavy rains which often occur during thunderstorms. Further research in this area would be useful in the field of weather modification technology, particularly, of the influence on clouds where the electrical characteristics in the neighborhood of the vertices can serve as an indicator of the state of the clouds exposed to such influence.